Analysis of the Use of Social Media as a Means of Spreading Hate Speech - Talitha Bea Amanda (Jurnal Indonesia Sosial Teknologi, 2024)
Hate speech in Indonesian is hate speech that cannot be precisely defined. Social media, in its definition is a platform that is used freely without pay, and any binding regulations. This freedom allows individuals who are constrained by the rules to voice their opinions through social media. Hate speech can target anyone indiscriminately. Victims of hate speech not only experience defamation but also get psychological injuries that can lead to death. There must be a binding battle for individuals who express their opinions too freely on existing platforms and have no legal provisions. Cooperation between nations is needed in the suppression of hate speech.